Standardization of Factor VIII – IV. Establishment of the 3rd International Standard for Factor VIII: C Concentrate - Barrowcliffe, T W; Curtis, A D; Thomas, D P (Thrombosis and Haemostasis, 1983)
An international collaborative study was carried out to establish a replacement for the current (2nd) international standard for Factor VIII: C, concentrate. Twenty-six laboratories took part, of which 17 performed one-stage assays, three performed two-stage assays and six used both methods. The proposed new standard, an intermediate purity concentrate, was assayed against the current standard, against a high-purity concentrate and against an International Reference Plasma, coded 80/511, previously calibrated against fresh normal plasma.Assays of the proposed new standard against the current standard gave a mean potency of 3.89 iu/ampoule, with good agreement between laboratories and between one-stage and two- stage assays. There was also no difference between assay methods in the comparison of high-purity and intermediate purity concentrates. In the comparison of the proposed standard with the plasma reference preparation, the overall mean potency was 4.03 iu/ampoule, but there were substantial differences between laboratories, and the two-stage method gave significantly higher results than the one stage method. Of the technical variables in the one-stage method, only the activation time with one reagent appeared to have any influence on the results of this comparison of concentrate against plasma.Accelerated degradation studies showed that the proposed standard is very stable. With the agreement of the participants, the material, in ampoules coded 80/556, has been established by the World Health Organization as the 3rd International Standard for Factor VIII :C, Concentrate, with an assigned potency of 3.9 iu/ampoule.
Keywords: Factor VIII; Concentrate; International Standard